Lectotypifications of three Duroia names (Rubiaceae, Gardenieae) of species occurring in Brazil - Nascimento, Janilde De Melo; Santos, João Ubiratan Moreira Dos; Conceição, Gonçalo Mendes; Pessoa, Edlley (Phytotaxa, 2019)
During ongoing studies of the Brazilian species of Duroia, three names were detected that need formal typification. Lectotypes for Duroia duckei, D. fusifera, and D. saccifera are designed here. For each species, updated data on the collection localities (current city/state) are provided, along with the exact text of the protologue or type label, along with a discussion of the history of these names.